ANALISIS SEKTOR UNGGULAN TERHADAP PEMBANGUNAN WILAYAH DI KABUPATEN KLATEN - Diah Tri Rohmawati; Farisa Maulinam Amo (Universitas Muhammadiyah Gorontalo, 2025)
Economic planning and economic growth are an inseparable unity. Economic science in planning is focused on analyzing and examining the problems faced by a region. Economic growth and development in a region can be identified through sectors that have the potential to become leading sectors in that area. One way to identify leading sectors in a region is by analyzing Gross Regional Domestic Product (GRDP) data over time.The socio-economic conditions of the people of Klaten Regency have experienced significant changes and rapid progress. Development has created various economic activities and sources of income, which in turn are able to improve community welfare and living standards. The dependent variable (Y) in this study is regional development, while the independent variable (X) is the leading sector. The analytical methods used to determine potential leading and non-leading sectors in Klaten Regency include Location Quotient (LQ) analysis and Shift Share analysis, combined with Klassen Typology analysis. Based on the results of the study, Klaten Regency has several leading and non-leading sectors. Both types of sectors need to be taken into account so that development planning in Klaten Regency can be evenly distributed and able to increase the GRDP of Klaten Regency.